The Palgrave handbook of gendered violence and technology - Powell, Anastasia; Flynn, Asher; Sugiura, Lisa (Palgrave Macmillan, 2021)
1. Gender, Violence And Technology: At A Conceptual And Empirical Crossroad, Anastasia Powell, Asher Flynn And Lisa Sugiura -- 2. ‘Cummunity Standards’: Resisting Online Sexual Harassment And Abuse, Morgan Barbour -- 3. Legal Possibilities & Criminalized Population Groups: A Personal Experience Of An Indigenous Woman In The Sex Trade, Naomi Sayers -- 4. Sexual Predators Cannot Break My Spirit: A Story Of Fighting Back Against Technology-Facilitated Abuse, Noelle Martin -- 5. From Individual Perpetrators To Global Mobilisation Strategies: The Micro-Foundations Of Digital Violence Against Women, Lilia Giugni -- 6. Alternate Realities, Alternate Internets: African Feminist Research For A Feminist Internet, Neema Iyer -- 7. Culturally And Linguistically Diverse (CALD) Women’s Experiences Of Technology-Facilitated Violence: An Intersectional Approach, Carolina Leyton Zamora, Jennifer Boddy, Patrick O’Leary And Joe Liang --
Keywords: Sexuelle Belästigung; Geschlechtersoziologie; Social Media; Sexualisierte Gewalt; Computer crimes; Critical criminology; Criminology; Sociology; Social policy; Welfare state; Aufsatzsammlung